South Asia’s Digital Opportunity : Accelerating Growth, Transforming Lives - World Bank (Washington, DC: World Bank, 2022)
The report presents both the opportunities of and the bottlenecks for furthering the digital agenda. It emphasizes that the first step is to get the basics right. This includes enabling access to and adoption of high-quality affordable broadband, initiating a paradigm shift in building digital public platforms and accelerating digital financial services. Part of this includes integrating digital ID, digital payments, and data sharing platforms so they can become ‘digital stacks’ that allow service providers to build and innovate their own platforms and systems on top. Supporting digital businesses, fostering digital skills, and creating the necessary trust environment are also critical to the digital agenda. Further, a successful digital agenda at country levels would benefit from regional integration that entails cross-border connectivity, data infrastructure, and payment systems.